Clinical Evaluation of Stainless Steel and Titanium Elastic Nails for Femur Fracture Repair in Young Dogs - R, Swaroop; D R, Manjunatha; N, Nagaraju; S, Ganga Naik; V , Shivakumar; V T, Shilpa; N M, Ramya (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The cross-pollination of knowledge between human and veterinary orthopaedics continues to advance the field, facilitating the development of innovative treatment options for musculoskeletal disorders in animals. This comparative study seeks to delve into the clinical implications and biomechanical aspects associated with the use of two different elastic nails for femur fracture repair in young dogs. The current study involved 12 clinical cases with femoral fractures in dogs of various breeds and genders. Six dogs each were treated with titanium and stainless-steel elastic nails, respectively. Signalment and history were collected which was followed by clinical and radiographic examination to assess the fracture characteristic. Post-operative lameness, radiographic evaluations and complications were recorded on 15th, 30th and 45th post-operative days. Clinical efficacy was notably superior by using titanium elastic nails (TENs). This was evident in terms of ease of application intraoperatively, early weight bearing, reduced surgical duration, suitability for both diaphyseal and distal femoral fractures. However, stainless steel elastic nails (SSENs) were found to be well suitable for diaphyseal transverse femur fractures and offer the advantage of being less expensive.